2008
DOI: 10.1017/s0007114508003097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a combination ofLactobacillus acidophilusNCFM and lactitol on healthy elderly: intestinal and immune parameters

Abstract: With increasing age, a number of physiological changes take place which are reflected in immune and bowel function. These changes may relate to the commonly assumed age-related changes in intestinal microbiota; most noticeably a reduction in bifidobacteria. The current study aimed at modifying the intestinal microbiota with a potential synbiotic on selected immune and microbiota markers. Healthy elderly subjects were randomised to consume during 2 weeks either a placebo (sucrose) or a combination of lactitol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 35 publications
4
125
0
1
Order By: Relevance
“…Similarly to other sugar alcohols, it also does not contribute to dental caries [10,45]. Lactitol also acts as a prebiotic that is capable of promoting the growth of beneficial bacteria in the colon such as Bifidobacteria and Lactobacilli, but also reduces the population of putrefactive bacteria selectively and lowers the intestinal pH as well as the production and absorption of ammonia [45,46,48,50,51]. Lactitol was also applied in treating encephalopathy and constipation [52][53][54][55][56].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Similarly to other sugar alcohols, it also does not contribute to dental caries [10,45]. Lactitol also acts as a prebiotic that is capable of promoting the growth of beneficial bacteria in the colon such as Bifidobacteria and Lactobacilli, but also reduces the population of putrefactive bacteria selectively and lowers the intestinal pH as well as the production and absorption of ammonia [45,46,48,50,51]. Lactitol was also applied in treating encephalopathy and constipation [52][53][54][55][56].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…26 Also, inulin-type fructans may contribute to cholesterol reduction by increasing fecal bile acid excretion, reducing intestinal cholesterol absorption, as well as increasing of the expression of 3-hydroxy-3-methylglutaryl-COA reductase (HMG-COA reductase). 27 Their impact on TLR4 signaling and proinflammatory cytokines might be explaining the role of their lipid lowering. 28 Prebiotics might also improve glycemic status via increasing insulin sensitivity with their impact on gene expression which involved in reduction of inflammatory activity and adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…12 immune parameters. One study found that faecal levels of PGE 2 were significantly increased in elderly subjects (≥ 65 years) after 2 weeks consumption of lactitol and L. acidophilus NCFM, as well as increases in bifidobacteria numbers (Ouwehand et al, 2009). This indicates an improvement in mucosal function and possibly the mucosal immune system which can impact on circulatory immune cells.…”
Section: Prebioticsmentioning
confidence: 99%